Male Reproductive Tract Origin Sperm-quiescent Proteins: Prospects in Semen Cryopreservation of Livestock Species - Paul, Rajani K; Chandel, Rajeev; Onteru, Suneel K (Animal Reproduction Update, 2021)
Cauda epididymis is known to preserve mature sperm in a quiescent state for several weeks without causing potential decline to fertilizing capacity of the sperm. This unique property of cauda epididymis has been attributed to the unique biochemical composition of cauda epididymal plasma and the presence of certain proteins having decapacitating and motility–inhibitory activities. Cryo-capacitation and low progressive motility are two common changes in cryopreserved semen across species and have been considered the underlying causes for low fertility rate of cryopreserved semen. Considering their potential roles in reversible inhibition of sperm capacitation and motility these naturally-occurring proteins may be suitable tools for minimizing cryo-capacitation and improving post-thaw progressive motility of cryopreserved semen by sparing available energy in sperm during cryopreservation. The present review attempts to bring out the status of purification, functional and mechanistic characterization of these sperm-quiescent proteins across species. In addition the status of recombinant production of these proteins by using different host systems and the scope for application of these proteins in semen cryopreservation of livestock species has also been described.
Keywords: Sperm-quiescent proteins; Purification; Mechanism of action; Recombinant production; Scope in semen preservation